Flood risk pattern recognition using integrated chemometric method and artificial neural network: A case study in the Johor River Basin - Saudi A.S.M.; Azid A.; Juahir H.; Toriman M.E.; Amran M.A.; Mustafa A.D.; Azaman F.; Kamarudin M.K.A.; Madihah Mohd Saudi (Penerbit UTM Press, 2024)
Indexed by Scopus